2010
DOI: 10.1177/0149206310365901
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High-Performance Human Resource Practices on Employees’ Attitudes and Behaviors

Abstract: Although strategic human resource (HR) management research has established a significant relationship between high-performance HR practices and firm-level financial and market outcomes, few studies have considered the important role of employees’ perceptions of HR practice use or examined the more proximal outcomes of high-performance HR practices that may play mediating roles in the HR practice–performance relationship. To address recent calls in the literature for an investigation of this nature, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
1,157
1
20

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 988 publications
(1,231 citation statements)
references
References 64 publications
53
1,157
1
20
Order By: Relevance
“…It is specifically relevant to study the latter because these collective subjective experiences with job characteristics are closer to employee reactions than managerial intentions (Kehoe and Wright, 2013). We thus study employees' perceptions of job characteristics in the aggregate (at the job group level).…”
mentioning
confidence: 99%
“…It is specifically relevant to study the latter because these collective subjective experiences with job characteristics are closer to employee reactions than managerial intentions (Kehoe and Wright, 2013). We thus study employees' perceptions of job characteristics in the aggregate (at the job group level).…”
mentioning
confidence: 99%
“…Piening, Baluch & Salge, 2013). Prior research found that the perceived intensity of HRM systems is positively related with employee task performance (Kooij, Jansen, Dikkers, & De Lange, 2010;Kuvaas & Dysvik, 2010) and OCB (Alves, Shantz, Truss, & Soane, 2013;Kehoe & Wright, 2013). Given that employee perceptions of HRM systems follow from the degree to which employees co-produce them, we predict a relationship between HRM coproduction and employee performance, which is mediated by the employee reports of HRM systems.…”
Section: Relating Hrm Co-production To Employee Perceptions Of Hrm Anmentioning
confidence: 81%
“…As reflected in Hypothesis 1, higher levels of HRM co-production result into higher levels of perceived intensity of HRM systems by employees. Others have argued that these perceptions of HRM system intensity induce employees to engage in task performance and OCB (Kehoe & Wright, 2013;Kuvaas & Dysvik, 2010). In doing so, they have mostly build on the social exchange theory to conceptualize the performance effects of HRM practices (Blau, 1964).…”
Section: Relating Hrm Co-production To Employee Perceptions Of Hrm Anmentioning
confidence: 99%
See 1 more Smart Citation
“…These human resource practices results in the employee outcomes like employee's job performance, employee's job satisfaction, employee's turnover intention, and perception of procedural justice. Kehoe and Wright (2013) investigate the perception of employees towards the high performance human resource management practices that shows a positive relationship with the financial and market outcomes. The employee perception of high performance practices shows a positive relationship with the organizational citizenship behaviour, which is mediated by affective organizational commitment.…”
Section: Literature Reviewmentioning
confidence: 99%